The status of training for educational supervision courses at the Institute of Training and educational development from the point of view of the trainees (Journal of the College of Basic Education, 2023)
Despite the efforts made by the Ministry of Education to prepare the administrative and educational cadres And through courses and training programs that are held by the preparation and training directorates, the most prominent of which is the Institute of Training and educational development, but this does not mean reaching and rising to the level of ambition that we seek. And we need to update and renew the methods used in the training programs and ways to upgrade the courses.